Incidence of Salmonella spp. in raw vegetables in Selangor, Malaysia - Awang Salleh, Noorzaleha; Rusul, Gulam; Hassan, Zaiton; Reezal, Abdul; Hajar Isa, Siti; Nishibuchi, Mitsuaki; Radu, Son (Elsevier, 2003)
A total of 43 samples of ‘selom’ (Oenanthe stolonifera), 26 samples of ‘pegaga’ (Centella asiatica), 25 samples of ‘kangkong’ (Ipomoea aquatica) and 18 samples of ‘kesum’ (Polygonum minus) were examined for the presence of Salmonella spp. Salmonellae were detected from 40 (35%) of the vegetables samples examined. The most common serotypes isolated were S. weltevreden (23.5%), S. agona (16.2%), S. senftenberg (10.1%) and S. albany (6.7%). The other 27 Salmonella serovars were isolated at frequencies from 0.6% to 3.4%. Several of the Salmonella serotypes isolated in this study have been implicated in human infections in other countries. Although Salmonella species are frequently detected in foods of animal origin, the detection of 31 Salmonella serovars in four local salad vegetables in this study is not very encouraging, and supported the notion that these vegetables can be potential health hazards.